THE EFFECT OF INTERMITTENT FASTING ON TRIGLYCERIDE LEVELS IN THE WISTAR STRAIN WHITE RATS (RATTUS NORVEGICUS) DIABETES MELLITUS MODEL - Harahap, Huntari; indah ayu dia, Esa; Kusdiyah, Erny; Subhan, Rahmatika (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
Background:: In Indonesia, there is an increasing population prevalence with abnormal triglyceride levels. Reducing triglyceride levels in the blood can be done in various ways including taking drugs and changing healthy lifestyles. Diet intervention methods that can be done are very diverse, one of which is Intermittent Fasting 5:2. Methods: Experimental uses this type of analysis quantitative laboratory research in vitro using a pre-test and post-test group design. The population used in this study were 30 (Rattus norvegicus) Wistar with a body weight of 150-250 grams. Which were divided into 3 groups, Results: From the results of the paired T-Test. It proves that there was no significant difference in treatment groups A, B, and C which was marked by the statistical test results obtained p> 0.05 (insignificant). Conclusion: There was no difference in triglyceride levels before and after treatment with intermittent fasting type 5:2 white Wistar rats.